Survival of in-hospital cardiorrespiratory arrest: integrative review of the literature - Daiana Terra Nacer; Ana Rita Barbieri (Universidade Federal de Goias, 2015)
Many lives are lost by Cardiorrespiratory Arrest (CA)  in-hospital, but there are few studies about it. The objective of this study was to identify the available evidence in the literature about in-hospital CA survival. An integrative review of the literature conducted from the guiding question: what is the scientific evidence available in the literature related to survival of in-hospital CA? From the descriptors "Cardiac Arrest", "Cardiopulmonary ressuscitation" and "Survival". Selected studies were systematized in the categories: survival rate analysis; factors related to survival and survival rates. As a result, we observed few publications about the theme, varying survival rates, studies with divergent designs and absence of national studies, highlighting the use of Utstein Style registries in the studies. We concluded that guidelines advertisement have been contributing to global survival improvements, and in the Brazilian setting, there is a need to broaden registries about their practices and results.